Inhibition of ITGB1 enhance the anti-tumor effect of cetuximab in colorectal cancer cell. Issue 27 (2nd July 2020) - Yang, Xiaohui; Wang, Shuai; Yu, Weihua; Zheng, Yixiong; Wu, Yulian
Abstract: Background: Colorectal cancer is the second commonly seen cancer around the world and accounts for 13% of all human cancers. Among them, 25% of all case were diagnosed with metastasis and 50% occurs metastasis during the development of disease. Cetuximab is a chimeric monoclonal antibody against epidermal growth factor receptor, and is used for treatment of metastatic colorectal cancer alone or combined with chemotherapy or radiation therapy. Integrin-beta 1 (ITGB1), which is also known as CD29, and plays an important role in development of malignant cancers. However, the effect of ITGB1 in promoting the anti-tumor effect of cetuximab is not fully understand. Methods: The model of ITGB1 inhibition and overexpression was firstly constructed in LS174T cells, and the viability of cells in each group was detected using CCK-8 assay. The expression of key factors in tumor formation process at transcription level was detected using real-time quantitative polymerase chain reaction method. The expression of key proteins in metastasis process, cell apoptosis and activation of Ras/Raf/MEK signaling pathway was detected using western blotting analysis. And the concentration of key factors of in tumor formation process in cultured medium of LS174T cells were detected using enzyme-linked immunosorbent assay method. Results: We found that cetuximab could inhibit the proliferation of LS174T cells, and inhibition of ITGB1 enhanced this effect while overexpression of ITGB1 reduced this effect. We further found that cetuximab could inhibit the expression and secretion of extracellular matrix degradation related molecules in cultured medium and transcription level. Besides, we also found that the expression of key factors in angiogenesis and extracellular matrix degradation related proteins were also reduced after cetuximab treatment. These effects might be mediated by Ras/Raf/MAPK signaling pathway and enhanced after inhibition of ITGB1 expression. Conclusion: Inhibition of ITGB1 might be a new therapeutic method in colorectal cancer. Abstract : Supplemental Digital Content is available in the text